EVALUATING THE EFFECT OF NIGERIA ROAD SAFETY STRATEGY ON ROAD TRAFFIC CRASHES IN THE SIX GEO-POLITICAL ZONES USING 3k FACTORIAL DESIGN (FUDMA JOURNAL OF SCIENCES, 2022)
Road Traffic Crashes (RTCs) has become a major challenge and threat to human health and safety. This research was conducted to investigate the effect of Nigeria Road Safety Strategy (NRSS) on RTCs in the six geo-political zones of the country. The dataset used was obtained from the annual records of Federal Road Safety Commission (FRSC) over a five year period (2016 – 2020).The dataset was subjected to Bartlett’s test of Homogeneity assumption which was not violated. Duncan Multiple Range Test was carried out to evaluate the differences in the groups. Three levels of road traffic crashes (no of cases, total casualties, and number of people involved) in the two regions of the Northern (North-Central, North-East and North-West) and Southern (South-West, South - South and South - East) Nigeria with six geo-political zones were modeled by linear regression analysis, and further subjected to 32 Factorial Designs with Analysis of Variance (ANOVA), using R-statistical package. Results of the study shows that total cases and the corresponding number of people involved in RTCs in the two regions are significant. 97% and 96% of the total variations in RTCs were explained by the variations in geo-political zones in both regions respectively. This affirms the fact that the models for the two regions were different with the rate of RTCs higher in the northern region than in the southern region
Keywords: Factorial design, Interaction effect, Main effect, ANOVA, Replication